Impact of a COVID-19 outbreak in a long-term care facility in Barcelona, Spain: The role of a COVID-19 prevention and control program - Gabriel Vallecillo; Marta Anguera; Noemi Martin; Cristina González; Consol Serra; Juan Pablo Horcajad; Víctor Pérez (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
Background: COVID-19 outbreaks in long-term care facilities are a significant impact on infection rates and mortality rates of the residents. The study aimed to describe the effectiveness of a COVID-19 prevention and control (CPC) program in a long-term care facility. Methods: A CPC program, including social isolation, active symptoms screening for all residents and staff, SARS-CoV-2 testing for symptomatic individuals, droplet and contact isolation measures for asymptomatic residents, confinement of the unit and clinical care in a separate unit for patients, was implemented in a long-term care facility with two geriatrics and two psychiatric units, with aa total of 300 beds. The attack rate was calculated as the number of COVID-19 confirmed cases divided by the total number of exposed individuals and case fatality rate as the deceased COVID-19 cases divided by the total number of COVID-19 cases. Results: Two geriatric (unit-1 and 2) and one psychiatric (unit-4) units were affected by the outbreak. Attack rates were 26/47(55.3%) for unit-1, 15/29(51.7%) for unit-1and 11/46(23.9%) for unit-4. Case fatality rates were 3/25(12.0%) for unit-1 and 2/16 (12.5%) for unit-2 and no patient from the unit-4 died. Among healthcare professionals, total attack rate was 30/124(24.2%) with no differences between units. Viral pneumonia was present in 13(25%) residents and all healthcare professionals had mild COVID-19. Conclusions: Timely institution of a CPC program with close monitoring of all exposed individuals are essential to decrease the negative outcomes of COVID-19 outbreaks in long-term care facilities. Droplet and contact isolation for all residents is a useful alternative to wide-facility SARS-CoV-2 testing.